2015
DOI: 10.1371/journal.pone.0131951
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Increasing Neuromuscular Electrical Stimulation Current Intensity on Cortical Sensorimotor Network Activation: A Time Domain fNIRS Study

Abstract: Neuroimaging studies have shown neuromuscular electrical stimulation (NMES)-evoked movements activate regions of the cortical sensorimotor network, including the primary sensorimotor cortex (SMC), premotor cortex (PMC), supplementary motor area (SMA), and secondary somatosensory area (S2), as well as regions of the prefrontal cortex (PFC) known to be involved in pain processing. The aim of this study, on nine healthy subjects, was to compare the cortical network activation profile and pain ratings during NMES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 81 publications
3
57
0
Order By: Relevance
“…In our previous pilot study using a two channel time‐resolved fNIRS device and modeling methods to disentangle scalp from cerebral hemodynamic changes , we showed that during anodal HD‐tDCS a greater portion of the fNIRS O 2 Hb signals were derived from the scalp level skin blood flow changes in close proximity to the anode of the 4 × 1 electrode montage with a smaller proportion from the intracranial (cerebral) layer. In the present study, our findings of the grater spatial distribution of O 2 Hb int values within than outside the boundary of the 4 × 1 electrodes ( L in > L out ROI) were representing a direct tissue effect of the scalp‐applied HD‐tDCS electric field stimulating scalp afferents and skin blood flow changes with a smaller proportion from the intracranial (cerebral) layer neurovascular coupling.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous pilot study using a two channel time‐resolved fNIRS device and modeling methods to disentangle scalp from cerebral hemodynamic changes , we showed that during anodal HD‐tDCS a greater portion of the fNIRS O 2 Hb signals were derived from the scalp level skin blood flow changes in close proximity to the anode of the 4 × 1 electrode montage with a smaller proportion from the intracranial (cerebral) layer. In the present study, our findings of the grater spatial distribution of O 2 Hb int values within than outside the boundary of the 4 × 1 electrodes ( L in > L out ROI) were representing a direct tissue effect of the scalp‐applied HD‐tDCS electric field stimulating scalp afferents and skin blood flow changes with a smaller proportion from the intracranial (cerebral) layer neurovascular coupling.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the current evidence from literature (Tachtsidis & Scholkmann, ). Interestingly, scalp blood flow changes (especially in the [O 2 Hb] signal) have been also observed during stimulations of sensorimotor areas due to nonpainful and painful electrical muscle stimulations (Muthalib et al., ). It could be shown that these task‐related scalp blood flow changes took place and that correcting for them is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that ES could be an effective therapeutic intervention for diabetes‐associated muscle atrophy, as well as for disuse‐ and inflammation‐induced muscle atrophy. However, ES causes severe pain and discomfort, but the levels of pain and discomfort depend on current intensity . Therefore, because high‐intensity ES induces severe pain while attempting to induce strong muscle contraction, it is necessary to develop new therapeutic treatments using ES to prevent muscle atrophy in order to avoid severe pain and discomfort.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, low‐intensity resistance exercise during Bfr could reduce the risk of the progression of microvascular complications without increasing blood pressure . Low‐intensity ES can be used instead of low‐intensity resistance exercise and, if the current intensity is maintained at a low level, severe pain and discomfort can be avoided . Therefore, the combination of Bfr and low‐intensity ES may be an effective therapeutic treatment to prevent diabetes‐associated muscle atrophy by inhibiting the decrease in protein synthesis, even at low intensity ES.…”
Section: Introductionmentioning
confidence: 99%